Is Parasitic Infection a Buffer Against Metal Pollution? - Vidal-Soto, R (Cambridge University Press, 2025)
Metal pollution is a major global issue in aquatic environments, affecting environmental quality and potentially altering host-parasite dynamics. This study evaluates the buffering role of a larval trematode Himasthla sp. under experimental conditions to test the effect of copper (Cu) exposure on the survival of the marine snail Echinolittorina peruviana. Snails were collected from intertidal rocky pools over a two-month period from Coloso (23°45’S, 70°28’W), northern Chile, and identified as parasitized or unparasitized. Both groups were then exposed to Cu concentrations (3 and 6 mg/L). Kaplan-Meier curves were used to determine the percentage of survival over time and the respective confidence intervals (CI). A nested ANOVA was conducted to assess whether rediae abundance per snail varied by experiment time, snail status, and Cu concentration. Snail survival was affected by both Cu-concentrations, but the effect was greater at 6 mg/L. At 3 mg/L, 57% (CI: 49.9-66.6%) of unparasitized snails were alive at 192 h, while 56% (CI: 46.6-67.4%) of parasitized snails survived at 216 h. At 6 mg/L, 42% (CI:35-51%) of unparasitized snails survived at 192 h, while 48% of parasitized snails survived at 216 h (CI:39-59%). Regardless of Cu concentration, after 240 h, all unparasitized snails had died, while 15% of parasitized snails remained alive. Dead snails harboured 125±53 rediae, while survivors had 194±73 rediae, with no significant differences between treatments. Our results show that parasitized snails survived longer than unparasitized snails, suggesting a trade-off between parasitism and host survival in polluted environments. © The Author(s), 2025.